(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
In the digital era, the application of technology for classroom learning is urgently needed. Teachers are greatly helped by the availability of various digital tools because it can be used to support the students’ learning process. Teacher’s behavior and trust are important factors in determining the role and effectiveness of technology use in the classroom. However, with all the advantages and conveniences offered by digital tools, there are still challenges that must be faced by the teachers. This study aims to find out the perception of English teachers towards the use of digital tools in teaching English. The participants were English Education students at Universitas Terbuka who enrolled the Teaching English as Foreign Language (TEFL) courses. The method used in this research is qualitative and the data is collected by using questionnaire. This research is expected to provide recommendations on the development of teaching methods and teaching materials related to the digital tools.